Plant Growth Regulators - Frederick M. Fishel (EDIS)
Revised! PI-102, a 5-page fact sheet by Frederick M. Fishel, defines the term, “plant growth regulator,” addresses patterns of use for plant growth regulators, and provides a listing of plant growth regulators registered for use in Florida. Published by the UF Department of Agronomy, April 2009. Revised January 2015 and February 2018. Retired from active collection, February 11, 2021.